Unilateral Valsalva retinopathy as an initial presentation of pancytopenia: a case report - Ghazanfar, Altamash Shahriyar; Siddiqui, Rehman (Journal of the Pakistan Medical Association, 2026)
We report the case of a man in his 40s who presented to the ophthalmology clinic complaining of a black shadow in the centre of his right vision. He was diagnosed with Valsalva retinopathy and a complete blood count was performed, which revealed pancytopenia. The patient was admitted a few days later due to worsening of his symptoms and an extensive blood workup revealed folate and vitamin B12 deficiency. He got better after blood transfusions, folic acid supplementation, and intravenous B-complex (Neurobion: B1 100 mg, B6 100 mg, B12 1 mg). After three months of follow-up, the retinal haemorrhages had resolved and the patient’s vision had improved. This appears to be the first documented case of unilateral Valsalva retinopathy as an initial manifestation of pancytopenia. This case highlights the importance of a thorough eye examination and workup to reveal a potentially life-threatening condition. Keywords: Valsalva retinopathy, Pancytopenia, Megaloblastic anaemia, Multidisciplinary care.